Effectiveness of the Al-Qur'an Murottal Method in Reducing Labor Anxiety in First-Time Pregnant Women in Sleman Yogyakarta - Yessi Handriyani; Tasman Hamami; Akif Khilmiyah; Azam Syukur Rahmatullah; Mohd. Syahrul Bin Kamaruddin (Jurnal Pendidikan Agama Islam, 2024)
Purpose – This study explores the effectiveness of the Al-Qur'an murottal method in reducing labor anxiety in pregnant women with their first child in Sleman, Yogyakarta through the integration of spiritual aspects, prenatal education, and family support. Design/methods/approach – This study uses a phenomenological approach to understand the experiences of the first 7 pregnant women in Sleman, Yogyakarta who experience labor anxiety and evaluate the effectiveness of Quran recitations through in-depth interviews and observations. Findings – This study revealed that first-time pregnant women in Sleman experience various forms of anxiety, such as uncertainty about childbirth, fear of pain, and social pressure. The Al-Qur'an murottal method has been proven to be very effective in reducing anxiety, providing inner peace, and strengthening the spiritual bond between mother and baby. Consistency in listening to the Quran recitation, along with support from partners and family, plays an important role in reducing anxiety and improving quality of life. Informants reported improved sleep quality, reduced stress, and readiness for childbirth. This therapy also helps to overcome insomnia and boosts confidence. Quran recitation has been proven effective in improving emotional well-being during pregnancy. Research implications/limitations - This study shows that the Murottal Al-Qur'an method is effective in reducing anxiety and improving the mental well-being of pregnant women, and is recommended for integration into prenatal care, with the need for further research and medical education. Originality/value – This study contributes to spiritual-based prenatal care, but further research is needed to strengthen the findings and explore the long-term effects of Quran recitation therapy.